Translation and Validation of the Short Form of the Fear of Dental Pain Questionnaire in China - Wu, Lei; Buchanan, Heather; van Wijk, Arjen J. (Frontiers in Psychology, 2021)
The short form of the Fear of Dental Pain Questionnaire (s-FDPQ) is a validated measure developed to screen patients for their fear of pain associated with dental procedures. As there is a high prevalence of dental fear/anxiety in Chinese adults, the primary aim of our study was to translate the s-FDPQ into standard Mandarin and explore its reliability and validity with Chinese adults. The second aim of our study was to explore fear of dental pain (FDP) scores in relation to dental attendance, anxiety and gender. We translated the s-FDPQ using the forward-backward method. It was completed by 480 Chinese adults alongside the Modified Dental Anxiety Scale (MDAS; Chinese version) to test convergent validity. 109 participants completed the s-FDPQ again 14 days later to evaluate test-retest reliability. The Chinese s-FDPQ (s-CFDPQ) was internally consistent (alpha=0.87) and demonstrated convergent validity (r=0.73 when correlated with the MDAS). Test-retest reliability was good (ICC=0.86). Individuals who had never attended the dentist (22%) had higher FDP scores than those that had, even if they were not dentally anxious. Also, females reported higher FDP scores (p<0.001). These findings suggest that the s-CFDPQ is a reliable and valid measure for assessing fear of dental pain in Chinese adults. The s-CFDPQ could allow quick identification of individuals who are fearful of dental pain who may require specialist attention.